Molecularly Imprinted Porous Aromatic Frameworks Serving as Porous Artificial Enzymes. Issue 27 (21st May 2018) - Yuan, Ye; Yang, Yajie; Faheem, Muhammad; Zou, Xiaoqin; Ma, Xujiao; Wang, Zeyu; Meng, Qinghao; Wang, Lili; Zhao, Shuai; Zhu, Guangshan
Abstract: Artificially designed enzymes are in demand as ideal catalysts for industrial production but their dense structure conceals most of their functional fragments, thus detracting from performance. Here, molecularly imprinted porous aromatic frameworks (MIPAFs) which are exploited to incorporate full host–guest interactions of porous materials within the artificial enzymes are presented. By decorating a porous skeleton with molecularly imprinted complexes, it is demonstrated that MIPAFs are porous artificial enzymes possessing excellent kinetics for guest molecules. In addition, due to the abundance of accessible sites, MIPAFs can perform a wide range of sequential processes such as substrate hydrolysis and product transport. Through its two functional sites in tandem, the MIPAF subsequently manifests both hydrolysis and transport behaviors. Advantageously, the obtained catalytic rate is ≈58 times higher than that of all other conventional artificial enzymes and even surpasses by 14 times the rate for natural organophosphorus hydrolase ( Flavobacterium sp . strain ATCC 27551). Abstract : Molecularly imprinted porous aromatic frameworks (MIPAFs) are exploited to incorporate the full host–guest interaction of porous materials into artificial enzymes. Through a tandem sequence of two functional sites (substrate hydrolysis and product transport), the MIPAF material subsequently expresses both hydrolysis and transport behaviors.